1983
DOI: 10.1111/j.1600-0528.1983.tb01377.x
|View full text |Cite
|
Sign up to set email alerts
|

Explorative study of the motives for non‐utilization of the Danish Youth Dental Care Scheme

Abstract: The present study attempted to develop an explanatory model for the lack of preventive dental behavior as demonstrated by the non-utilization of the Danish Youth Dental Care Scheme (YDCS). A focused interview was conducted with young, working class men by two carefully trained and experienced interviewers. Analysis of the interviews showed that no single factor could explain non-utilization of the YDCS. Rather a complex of factors partly on the individual social-psychologic, psychologic and economic level and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
1

Year Published

1988
1988
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
1
5
1
Order By: Relevance
“…If a visit was made, it would then be up to the dentist to motivate the young adult to continue in the program and the young adult would automatically be registered as user. The higher utilization rate of women compared to men in the Private as well as in the Mixed group is in accordance with numerous other studies, whereas the lack of association with social background was unusual (1,8,9,18), It seems probable on the basis of the results for both the Mixed and the Private groups that family background and personal behavioral factors such as attitudes to and knowledge about dental care come into force in deciding who will utilize the dental services regularly, as pointed out by ANTOFT (1,2). These factors might become of less significance when the dental service is organized under conditions as described for the Public group.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…If a visit was made, it would then be up to the dentist to motivate the young adult to continue in the program and the young adult would automatically be registered as user. The higher utilization rate of women compared to men in the Private as well as in the Mixed group is in accordance with numerous other studies, whereas the lack of association with social background was unusual (1,8,9,18), It seems probable on the basis of the results for both the Mixed and the Private groups that family background and personal behavioral factors such as attitudes to and knowledge about dental care come into force in deciding who will utilize the dental services regularly, as pointed out by ANTOFT (1,2). These factors might become of less significance when the dental service is organized under conditions as described for the Public group.…”
Section: Discussionsupporting
confidence: 83%
“…Frequencies of regular. 'irregular users and dropouts/non-users respectively are given in Table 3, Logistic regression analysis of the frequency of use in the Mixed and the Private groups showed that both delivery program (P = 0,00) and sex {P = 0,00) had significant effect, whereas there was significant association neither between social background and utilization (P = 0,26) nor between self-assessment of teeth and utilization (P = 0,14), Odds ratios for utilization between the Private and the Mixed groups were: ORpnvait M. j Ki = 2,04 with estimated approximative 95%i confidence limits (1,32,3,16), After correction for delivery program, women had a higher probability of being regular or irregular users than men, ORw™., M™ = 3.43 (2,22,5,28),…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such time period would probably not be long enough to demonstrate any change in habits. However, it could also be an example of the lack of evidence of the links between knowledge and change in behaviour, as appropriate knowledge does not necessary guarantee desired behaviour (Douglass and Cole 1979, Antoft 1983, Petersen and N ortov 1994. This kind of information is not yet available from an adult Chinese population due to the lack of traditions concerning public health questionnaire surveys which are commonplace in Western countries.…”
Section: Discussionmentioning
confidence: 98%